Long-term in vitro Treatment of Metformin Altered Biological and Biochemical Properties of Cardiac Cells - Seenak, Pornthanate; Paiyabhroma, Nitchawat; Chotimon, Phatiwat; Mekrungruangwong, Titiporn; Roytrakul, Sittiruk; Kumphune, Sarawut (Naresuan University Journal: Science and Technology (NUJST); Vol 24 No 1 (2016): January-April 2016, 2016)
A cardiovascular complication from diabetes, especially ischemic heart disease (IHD), is a major cause of death in diabetic patients. Metformin is an effective anti-diabetic drug that has been used worldwide. Several studies have reported the cardioprotective effect of Metformin in an in vivo and ex vivo model. However, information on the biological alterations of long-duration treatment with Metformin at the cellular and molecular levels is still unclear. The purpose of this study was to demonstrate the effects of long-duration cardioprotective doses of Metformin treatment on the biological, biochemical and proteomes characteristics of cardiac cells. Rat cardiac myoblast cell lines (H9c2) were cultured for 30 days in Dulbecco’s modified Eagle’s medium (DMEM) in both the presence and absence of 3mM Metformin, which was optimized as a cardioprotective dose, in a simulated ischemia/reperfusion model. The changes in cell proliferation were determined by the characteristic of the growth curve and calculated populations doubling time (PDT). The cellular morphology was measured by F-actin cytoskeleton staining with phalloidin conjugated with TRITC and visualized under a fluorescence microscope. The phosphorylation of p38 MAPK was demonstrated by western blotting. The alteration of the expressed cellular protein was determined by a proteomics technique. The results showed that the long term effects of 3 mM Metformin was an increase of cell proliferation, decreased populations’ doubling time, slight disorganized actin, and decreased phosphorylation of the p38 MAPK level. In conclusion, the data suggested that the in vitro effect of long-duration Metformin treatment altered the biological, biochemical and proteome characteristics of the cardiac cells. Keywords: diabetes , metformin, longterm effects of metformin, cardiac cell, proteomics
Keywords: diabetes, metformin, longterm effects of metformin, cardiac cell, proteomics